2010
DOI: 10.21273/hortsci.45.9.1338
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plant Hormones and Distillation Water on Mints

Abstract: Steam distillation of essential oil crops produces residual distillation wastewater that is released into the environment. This study evaluated the effects of three plant hormones [methyl jasmonate (MJ); gibberellic acid (GA3); and salicylic acid (SA)] at three concentrations and the residual distillation water from 15 plant species applied as foliar spray on biomass yields, essential oil content, and essential oil yield of Mentha ×piperita ‘Black Mitcham’ and Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 10 publications
0
10
1
Order By: Relevance
“…For example, previous studies demonstrated that some plant hormones such as MJ may increase carvone concentration of 'Scotch' spearmint (Zheljazkov and Astatkie, 2011a). In another study, the application of MJ had no significant effect on essential oil content of 'Native' spearmint (Zheljazkov et al, 2010b). In the same study, the application of distillation water from wild bergamot (bee balm) (Monarda fistulosa L.) increased the essential oil content, whereas the distillation water of absinthe wormwood (Artemisia absinthium L.), lavender (Lavandula vera DC), and wild bergamot increased oil yields of 'Native' spearmint (Zheljazkov et al, 2010b).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…For example, previous studies demonstrated that some plant hormones such as MJ may increase carvone concentration of 'Scotch' spearmint (Zheljazkov and Astatkie, 2011a). In another study, the application of MJ had no significant effect on essential oil content of 'Native' spearmint (Zheljazkov et al, 2010b). In the same study, the application of distillation water from wild bergamot (bee balm) (Monarda fistulosa L.) increased the essential oil content, whereas the distillation water of absinthe wormwood (Artemisia absinthium L.), lavender (Lavandula vera DC), and wild bergamot increased oil yields of 'Native' spearmint (Zheljazkov et al, 2010b).…”
mentioning
confidence: 95%
“…'Native' spearmint is a major essential oil crop grown in the Midwest and in the northwestern United States (National Agricultural Statistic Service, 2009). However, 'Native' spearmint has a wide environmental adaptation, and recent studies demonstrated feasibility of growing it under the humid conditions of Mississippi (Zheljazkov et al, 2010a(Zheljazkov et al, , 2010b(Zheljazkov et al, , 2012a. Recent studies in Wyoming indicated that 'Native' spearmint can withstand the first fall frost and apparently could be developed as a crop for northern Wyoming at 1170 m a.s.l.…”
mentioning
confidence: 99%
“…Furthermore, this study compared DWW of 13 essential‐oil plants and extracts from two alkaloid‐containing plants ( D. innoxia and G. flavum ) to the effect of well known plant hormones (GA3, JA and SA) on spearmint essential oil composition. A recent study evaluated DWW from other essential‐oil crop species on peppermint and spearmint growth, but not on the essential oil composition 12. We have previously reported that DWW of Achillea millefolium, Ammi majus, Artemisia absinthium, Cymbopogon flexuosus, Cymbopogon martinii, Chrysanthemum balsamita , and Hypericum perforatum increased the essential oil content of peppermint, whereas DWW of Monarda fistulosa increased the oil content of spearmint 12…”
Section: Resultsmentioning
confidence: 91%
“…Distillation waste water (DWW) is a waste product from the steam distillation of essential‐oil crops 12. Currently, it is being released into streams and rivers, causing environmental concern.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation